Examining the Moderating Effect of Past Travel Satisfaction on Revisit Intention: A Case of Chinese Tourists Visiting Malaysia - Norzalita Abd AZIZ; Fei LONG (Communications of International Proceedings, 2020)
China has become the largest source market for global outbound tourism. Many countries, including Malaysia, are aiming to attract more tourists from China to boost their tourism sector, and how to convince tourists to come back is a vital issue to achieve the goal. The paper intends to investigate Chinese tourists’ intention to revisit Malaysia by applying the theory of reasoned action (TRA) and past travel satisfaction. PLS-SEM is used to analyze data from 276 respondents, and it is found that attitude, subjective norm and past travel satisfaction are significant factors influencing Chinese tourists’ revisit intention to Malaysia. However, past travel satisfaction does not have any moderating effect. Based on the findings, national tourism organizations, marketers and operators are suggested to provide customized travel itineraries to Chinese tourists so as to make them loyal to their destination.
Keywords: Chinese tourists; Malaysia; Revisit intention; Past travel satisfaction; TRA.